2015
DOI: 10.1128/aac.00459-15
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Mycobacterium abscessus to Antimycobacterial Drugs in Preclinical Models

Abstract: bOver the last 10 years, Mycobacterium abscessus group strains have emerged as important human pathogens, which are associated with significantly higher fatality rates than any other rapidly growing mycobacteria. These opportunistic pathogens are widespread in the environment and can cause a wide range of clinical diseases, including skin, soft tissue, central nervous system, and disseminated infections; by far, the most difficult to treat is the pulmonary form. Infections with M. abscessus are often multidrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
149
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(153 citation statements)
references
References 41 publications
4
149
0
Order By: Relevance
“…Early studies confirmed that most immunocompetent mouse strains result in clearance of Mabs in the first weeks after infection with Mabs isolates (Ordway et al, 2008; Bernut et al, 2014b; Obregón-Henao et al, 2015), making model development and selection challenging. In these earlier studies, C57BL/6 and leptin-deficient (Ob/Ob) mice infected with Mabs with a low-dose aerosol inoculum (LDA, ~100 bacilli per mouse) did not develop a sustained progressive infection.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies confirmed that most immunocompetent mouse strains result in clearance of Mabs in the first weeks after infection with Mabs isolates (Ordway et al, 2008; Bernut et al, 2014b; Obregón-Henao et al, 2015), making model development and selection challenging. In these earlier studies, C57BL/6 and leptin-deficient (Ob/Ob) mice infected with Mabs with a low-dose aerosol inoculum (LDA, ~100 bacilli per mouse) did not develop a sustained progressive infection.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding M. abscessus infection, in vitro DST studies demonstrated a low MIC of CFZ and in vitro synergy between CFZ and other antibiotics, such as clarithromycin (CLR), AMK, or tigecycline (23)(24)(25)(26)(27)(28). The antimycobacterial activity of CFZ against M. abscessus was also demonstrated in vivo with Drosophila melanogaster and mouse models of infection (29,30).…”
mentioning
confidence: 96%
“…Bedaquiline also showed activity in the lung tissue of M. abscessus-infected mice [11]. The combination of bedaquiline and clofazimine showed a stronger synergistic effect; this combination therapy significantly lowered bacterial burden of M. abscessus in organs of interferongamma knockout (GKO) mice [8]. These animal models mimic disseminated rather than pulmonary NTM disease and like the HFM findings for MAC and M. abscessus, they still await confirmation in clinical trials.…”
mentioning
confidence: 99%
“…The new antituberculosis drug bedaquiline proved bacteriostatic against M. avium in a mouse model, but it did not add to the activity of macrolides [7]. Perhaps, in synergistic combinations (like the bedaquiline-clofazimine combination already proven synergistic in mouse models of M. abscessus disease) [8] bedaquiline might still prove helpful in MAC pulmonary disease (MAC-PD) treatment.…”
mentioning
confidence: 99%